The Effect of Transformational Leadership on the Implementation of the Triple Bottom Line in MSMEs - Asraf, Asraf; M. Budihard, Andi; Nurhayati, Ami; Hamida, La Ode (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Transformational leadership has been recognized as an important approach in contemporary management that encourages employee inspiration, motivation, and empowerment to achieve common goals. In the Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia, the Triple Bottom Line (TBL) concept that includes economic, social, and environmental aspects is becoming increasingly important but still faces many challenges in its implementation. This study aims to fill the knowledge gap about the influence of transformational leadership on the implementation of TBL in MSMEs. The study used a descriptive analytical approach with a survey method to collect data from MSME owners and employees who have implemented TBL principles. The results showed that transformational leadership has a significant positive impact on the implementation of TBL in MSMEs, with factors such as individual and team learning orientation and creative self-efficacy acting as mediators that strengthen the relationship. In addition, HR training and development factors and leader support were found to be key elements that influence the effectiveness of TBL implementation. The implications of this study emphasize the importance of the role of transformational leadership and learning culture in supporting MSME business sustainability, as well as providing practical guidance for MSME leaders to achieve economic, social, and environmental sustainability goals.